1998
DOI: 10.1074/jbc.273.14.8516
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Factor VII Gln100 → Arg

Abstract: We have used recombinant mammalian expression and purification of the factor VII (FVII) variant Gln 100 3 Arg (Q100RFVII) to study FVII deficiency in subjects with this mutation. Q100RFVII was secreted poorly in comparison with wild-type FVII (WTFVII) in a stable mammalian expression system, and purified variant protein was found to have undetectable clotting activity. Following activation by immobilized factor Xa, Q100RFVIIa had amidolytic activity similar to WTFVIIa in the absence of soluble tissue factor (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…Before treatment, FXaG was barely detectable in conditioned medium from cells expressing rFVII-160R. This is in agreement with data published by Kemball-Cook et al [10], who showed that the activated form of the mutant recombinant protein had reduced affinity for TF and, in the presence of soluble TF, had less than 5% of the ability of rFVIIwt to activate FX. Accordingly, evaluation of the FXa generation parameters before 4-PBA treatment was not feasible because mutant curves were not suitable for quantitative analysis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Before treatment, FXaG was barely detectable in conditioned medium from cells expressing rFVII-160R. This is in agreement with data published by Kemball-Cook et al [10], who showed that the activated form of the mutant recombinant protein had reduced affinity for TF and, in the presence of soluble TF, had less than 5% of the ability of rFVIIwt to activate FX. Accordingly, evaluation of the FXa generation parameters before 4-PBA treatment was not feasible because mutant curves were not suitable for quantitative analysis.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand the specific activity of the 4-PBA-induced rFVII-160R was still considerably reduced compared to rFVIIwt, as expected for FVII molecules bearing important structural changes. Particularly, the replacement of the glutamine side chain by the larger, positively charged arginine side chain in FVII-160R would disrupt hydrogen bonding networks and destabilize protein inter-domain areas [10]. It is tempting to speculate that folding disturbances in the EGF-2 protease region of FVII-160R, probably responsible both for barely detectable affinity for TF and for the secretion defect, would be partially overcome by the 4-PBA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retention of the overall fold of this domain on solvation is not surprising, because it has been shown that the EGF-like domains of FVIIa remains stable under high guanidine hydrochloride concentrations and at elevated temperatures. 59 The mutation Gln100 → Arg in the EGF2 domain has been detected 60 -62 61 using surface plasmon resonance. The outcome was severely reduced binding of the mutant of both FVII and FVIIa to TF.…”
Section: Egf2 Domainmentioning
confidence: 99%
“…1A). We thenattemptedtoexpress recom-binant mouse TF 1-225 using the same system as we had used for recombinant hTF (1),h owever no mTF wasp roduced. We thenimmunised rabbits with synthetic peptidesderivedfrom the mTF extracellulard omains (including one previouslyr eported to generate an effective anti-mTF antibody(2)).All the peptides induced an immune response and the antisera specifically recognised the linear peptide sequence, howevertheyreacted poorly withmouse TF expressed by murine fibroblasts in Westernblot, immunohistochemical and flow cytometric analyses (datan ot shown).W ehavenow circumvented these problems by using a simple nucleic acidi mmunisation method to generate ar abbit polyclonalanti-mTF antibody that is effective in detecting both recombinanta nd native mTF in av arietyo fe xperimental settings.…”
Section: Introductionmentioning
confidence: 99%